Peningkatan Kapabilitas Pemasaran Pascabencana Bagi Perempuan Hunian Tetap Pager Jurang, Sleman, Yogyakarta - Bevaola Kusumasari; Hempri Suyatna (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2015)
Disaster is a natural phenomenon which has become part of everyday human life. The amount of material and non-material losses arising from any catastrophic event raises concerns together. Women are one of the most vulnerable people to disaster. However, women have shown their potential capability to become agents of change if managed purposely. Women Pager Jurang, Sleman, Yogyakarta have done a good adaptation in post-disaster life by developing entrepreneurial skill in selling food products and crafts to increase their income. However, marketing knowledge has become their constraints to make their efforts sustained. This paper aims to describe community service activities in order to improve the capability of women in marketing knowledge. The activity used for community service were included training on marketing, financial capital, and institution, advocacy, and community assistance. The program has shown positive impacts on the marketing capability and networking for women in Pager Jurang.